2014
DOI: 10.1371/journal.pone.0111934
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Breast Cancer in Taiwanese Women: Potential Treatment Delay and Impact on Survival

Abstract: This study investigated the clinicopathologic characteristics and survival of women diagnosed with pregnancy-associated breast cancer (PABC) in Taiwan. PABC is defined as breast cancer diagnosed during pregnancy or within 1 year after obstetric delivery. Our sample of PABC patients (N = 26) included all patients diagnosed at a major medical center in northern Taiwan from 1984 through 2009. Among these patients, 15 were diagnosed during pregnancy and 11 were diagnosed within 1 year after delivery. The compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
0
24
1
1
Order By: Relevance
“…The previous Taiwanese study showed that patients with antepartum breast cancer usually waited more time before initiating treatment than those with postpartum or nonpregnancy‐related cancer . The authors suggested that the patients may choose to delay treatments because of concerns for the baby's health .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The previous Taiwanese study showed that patients with antepartum breast cancer usually waited more time before initiating treatment than those with postpartum or nonpregnancy‐related cancer . The authors suggested that the patients may choose to delay treatments because of concerns for the baby's health .…”
Section: Discussionmentioning
confidence: 99%
“…Only three East Asian studies have examined this problem . One study collected data from a hospital in northern Taiwan from 2004 to 2009 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence it is not advised anymore, but if breast cancer is diagnosed in the early stage of gestation, cessation of pregnancy may become a more viable choice considering the risks associated with a delay in standard treatment [39]. In general, the fiveyear survival rate in PABC is similar to the non-pregnant population; however, two primary risk factors which may affect the survival rate of PABC are a history of recent pregnancy and delay in treatment for 3 to 6 months [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%